Stakeholders’ attitudes towards continued dispensing - Abukres, Salem Hasn (Curtin University, 2015)
This study aimed to explore stakeholder’s attitudes towards Continued Dispensing (CD), a new method to supply Statins and Oral Contraceptives without a valid prescription. Consumers and pharmacists were supportive of CD, however both felt expansion of the range of medications covered could occur. At an organisational level doctors oppose CD, however at an individual level this was not evident. The results suggest CD appears to be a positive initiative with scope for possible expansion.